Perspectives, advantages, and limitations of vanadium oxides for batteries, energy storage applications, gas sensors and electrochromic devices: a comprehensive mini-review - Guerrero-Pérez, María Olga (Wiley, 2025)
Since many decades ago, it is known that V oxides may be conductive, in addition to other interesting properties, as the ability to insert/extract cations and to form mixed valence oxides of different colors, which make them useful for the fabrication of devices in which electrons and cation transport are required, as well as batteries, supercapacitors, sensors, and electrochromic devices. This contribution documents, from a historical perspective, the advancements that have been made in the use of V-oxide-based materials in these devices with a detailed discussion on their synthesis methods, phases formed, and analysis of the applications to offer a coherent synthesis on the relationships between the structure and the behavior of the V-based devices for energy applications.
Keywords: Energía - Almacenamiento; Pentóxido de vanadio; Sistemas de almacenamiento; Baterías; Óxidos de vanadio